Efektivitas Fitoremediasi Kayu Apu (Pistia Stratiotes L.) Dalam Memperbaiki Kualitas Air - Prahmawati Pujiyanti Kusuma Dewi; Kharisma Putri Maharani; Leony Putri Yuliana; Ambar Kurnia Sari (UNIVERSITAS PGRI MADIUN, 2023)
Water is a natural resource that is important for life. However, many rivers in Indonesia experience pollution problems. One alternative for handling water pollution is to use phytoremediation plants such as kayu apu. The aquatic plant kayu apu (Pistia stratiotes L.) is known to have phytoremediation capabilities to clean up pollution. However, there is still little research that focuses on the influence of environmental factors on its capacity to improve water quality. Therefore, this research project aims to determine the ability of kayu apu as a phytoremediator in reducing the concentration of pollutants and improving water quality. The method used is a post-test only control group design. Water samples were taken in the Bantaran River, Madiun, then incubated with apu wood plants. The parameters tested include Ph, temperature and water condition (turbid/clear). The research results show that kayu apu is able to reduce the concentration of pollutants and improve water quality through a phytoremediation mechanism. It is hoped that this project can increase understanding regarding the potential of the kayu apu plant as a phytoremediator in efforts to preserve aquatic ecosystems and their biodiversity